Demonstration of Improved Elephant/Napier grass (Pennisetum purpureum) Technologies for Animal Feed Resources in Dire Dawa and Harari Region rural areas - Abdulaziz Teha Umer; Ibsa Aliyi Usmane (Global Journal of Ecology - Peertechz Publications, 2020)
Two Elephant grass IRLI14983 and local check varieties were demonstrated and evaluated for their biomass traits under diverse environmental conditions of Harari and Dire Dawa. The study was conducted in four kebeles Dodota and Kile from Harari and Wahil and Bishan Bahe from Dire Dawa. From each kebeles ten (10) farmers in total of forty (40) farmers participated in this research activity. This research found that there was biomass yield statistically significance difference at (P<0.01) among the demonstrated varieties. And the yield of IRLI14983 ranged from 6.7 to 12.9 t/ha with a mean of 9.8 t/ha whereas local variety gave the 4.3ton/ha and 9.1 ton/ha biomass yield across the sites as comparison. In addition, Elephant/Napier grass varieties responded differently across the demonstrated environments due to differential responses of the climatic and biotic factors. The highest record was at Dodota (10.62 t/ha) followed by Wahil (9.61 t/ha) in comparison with the rest sites Kile and Bishan Bahe because of field management and other climate conditions. Therefore, it is better to promote to other similar agro-ecology with these sites by Government, Non-government and other stakeholders through their programs.